Realisasi Dana Bantuan Langsung Tunai (BLT) Dalam Membantu Perekonomian Masyarakat Pada Masa Pandemi Covid-19 di Kabupaten Tanah Datar - Fatmawati; Listiawati; Rosmita; Silvia, Ima Lailatul (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research departs from the background of the Nagari Padang Laweh Government implementing the Direct Cash Assistance program to help the community's economy. The Direct Cash Assistance Program is given to people who are the target recipients of BLT, according to Permendes and Pernag. The problem of this research is how the Nagari Government realizes the Cash Direct Assistance Fund and whether it is following the rules set by the Central Government. The purpose of the study was to find out how the Realization of Direct Cash Assistance Funds in Helping the Community Economy During the Covid-19 Pandemic In Nagari Padang Laweh, Sungai Tarab District, Tanah Datar Regency. This qualitative research uses a descriptive approach, and data collection techniques used by the author are interviews, observation, and documentation. Informants in this study amounted to 12 people. Then the data is analyzed through data collection, reduction, presentation, and conclusions. The result of this research is that there are three indicators in the realization of the Cash Direct Aid Fund. First is the process of making it real, in which data collection is carried out by the target community of the assistance recipient. Second, the realization of the BLT program has several obstacles, namely the Nagari Government's inaccuracy in funds. Several procedures must be met in disbursing funds. Third, the actual implementation of the Direct Cash Assistance program regarding the timeliness depends on the Village Fund that goes into the Nagari account. In this real implementation, the achievement of the program has been achieved because the Beneficiary Families feel helped by the existence of this Cash Direct Assistance Program.